Targeted treatment of folate receptor-positive platinum-resistant ovarian cancer and companion diagnostics, with specific focus on vintafolide and etarfolatide - Serpe L; Gallicchio M; Canaparo R; Dosio F (Dove Medical Press, 2014)
Loredana Serpe, Margherita Gallicchio, Roberto Canaparo, Franco DosioDepartment of Drug Science and Technology, University of Turin, ItalyAbstract: Among the gynecological malignancies, ovarian cancer is the leading cause of mortality in developed countries. Treatment of ovarian cancer is based on surgery integrated with chemotherapy. Platinum-based drugs (cisplatin and carboplatin) comprise the core of first-line chemotherapy for patients with advanced ovarian cancer. Platinum-resistant ovarian cancer can be treated with cytotoxic chemotherapeutics such as paclitaxel, topotecan, PEGylated liposomal doxorubicin, or gemcitabine, but many patients eventually relapse on treatment. Targeted therapies based on agents specifically directed to overexpressed receptors, or to selected molecular targets, may be the future of clinical treatment. In this regard, overexpression of folate receptor-α on the surface of almost all epithelial ovarian cancers makes this receptor an excellent "tumor-associated antigen". With appropriate use of spacers/linkers, folate-targeted drugs can be distributed within the body, where they preferentially bind to ovarian cancer cells and are released inside their target cells. Here they can exert their desired cytotoxic function. Based on this strategy, 12 years after it was first described, a folate-targeted vinblastine derivative has now reached Phase III clinical trials in ovarian cancer. This review examines the importance of folate targeting, the state of the art of a vinblastine folate-targeted agent (vintafolide) for treating platinum-resistant ovarian cancer, and its diagnostic companion (etarfolatide) as a prognostic agent. Etarfolatide is a valuable noninvasive diagnostic imaging agent with which to select ovarian cancer patient populations that may benefit from this specific targeted therapy.Keywords: vintafolide, etarfolatide, platinum-resistant ovarian cancer, targeted therapy, biomarkers, folate receptor